Respuesta :

The standard form of a quadratic equation is :

ax² + bx + c = 0

And the quadratic formula is:

x=\frac{-b\pm\sqrt{b^2-4ac}}{2a} .

So, first step is to compare the given equation with the above equation to get the value of a, b and c.

So, a = -1, b = 2 and c = 1.

Next step is to plug in these values in the above formula. Therefore,

[tex] x=\frac{-2\pm\sqrt{(2)^2-4*(-1)*(1)}}{2*(-1)} [/tex]

[tex] =\frac{-2\pm\sqrt{4+4}}{-2} [/tex]

[tex] =\frac{-2\pm\sqrt{8}}{-2} [/tex]

[tex] =\frac{-2\pm\sqrt{4*2}}{-2} [/tex]

[tex] =\frac{-2\pm\sqrt{4}*\sqrt{2}}{-2} [/tex]

[tex] =\frac{-2\pm2*\sqrt{2}}{-2} [/tex]

[tex] =-\frac{-2}{-2} \pm\frac{2\sqrt{2}}{-2} [/tex]

So, x =[tex] 1 \pm\sqrt{2} . [/tex]

Answer:1+

Step-by-step explanation:

the answer to

ACCESS MORE